Public health implications of low birth weight - Mata Jiménez, Leonardo (1977)
The present paper interpets the significance of anthropometric data of newborns from a typical Indian village of Guatemala and from the general population of Costa Rica. A good correlation exists between a deficient fetal growth and infant mortality and retarded physical growth. The significance of fetal growth retardation on early and late llnomalics and defects is discussed. The existing information reveals a high incidence of neonates with altered fetal growth and development in Latin America. This circumstance is the main factor . associated with the high infant mortality and retarded development observed in many populations of the Subcontinent. Presented at': Colloquium on "Prenatal and Perinatal Nutrition", held as part of the IV Latin American Nutrition Congress, Caracas. Venezuela, 21-27 Novar. bert 1976, under the sponsorship of the Latin American Nutrition Society (SLAN) Certain countries have attained a substantial improvement in the conditions affecting fetal growth, by implementing comprehensive health and development programs with a holistic approach. The interventions that need to be strengthened in order to improve fetal development in our nations are reviewed.